FORMULASI DAN EVALUASI ANTIBAKTERI TABLET HISAP EKSTRAK CABE JAWA (Piper retrofractum Vahl.) METODA GRANULASI BASAH - Ardian Baitariza (Jurnal Sabdariffarma: Jurnal Ilmiah Farmasi, 2026)
The research about antibacterial lozenges formulation from Cabe Jawa (Piper retrofractum Vahl.) dry extract by wet granulation method has been carried out. This research was to obtain a well criteria antibacterial  lozenges formulation as pharmaceutical dosages form which can be accepted by society. Lozenges formula made in three formulation with various concentrations of sweeteners, fillers, binder and different lubricant. Products were analyzed its physical properties of the granules (water contain, flow rate, and compressibility), tablet physical properties (hardness, friability, solubility time, size and weight uniformity), organoleptic properties (shape, smell, color and taste), piperine content and antibacterial activity of each tablet. The test results showed that all formulas tablet been eligible as antibacterial lozenges. Formula A been the best result of the physical properties and levels of analysis, whereas the response in terms of flavor formula B and been  preferred in terms of organoleptic appearance is the formula C.